요소 , 멜라민 접착제의 수지 조성에 따른 마루판의 천연무늬단판 접착성 및 포름알데히드 방출에 대한 연구 - 강은창; Eun Chang Kang; 박종영; Jong Young Park; 박헌; Heon Park (목재공학, 2002)
This study was to investigate the adhesion properties of fancy veneer and base panels and formaldehyde emission of wood-based floorings bonded with urea-melamine formaldehyde adhesives. We focused on stoichiometric mole ratio of reactive functional groups. The urea-melamine formaldehyde adhesives were made at twelve different formaldehyde/urea-melamine mole ratios. The interlaminated shear strength and formaldehyde emission of wood-based floorings bonded with selected adhesive among these adhesives were examined. The results showed that the bonding properties were high and the formaldehyde emission was low as the adhesive consisted of stoichiometric mole ratio of formaldehyde/urea-melamine. Interlaminated shear strengths of HDF(High Density Fiberboard) flooring were over 14 kgf/cm2 at all mole ratios. At the mole ratio of 1.0, HDF flooring showed low value of formaldehyde emission of 953 mg/L. Interlaminated shear strengths of Plywood flooring were high, 14.02 kgf/cm2 at mole ratio of 1.4. At the mole ratio of 1.0, Plywood flooring showed low value of formaldehyde emission of 0.26 mg/L. 본 연구는 마루판의 천연무늬단판 접착에 이용되고 있는 요소-멜라민 접착제의 수지조성에 따른 접착성능 및 포름알데히드 방출량의 변화를 알아보고자 하였다. 요소에 멜라민에 대한 포름알데히드의 몰비 1.0, 1.1, 1.2, 1.4를 기준으로 제조된 접착제로 마루판용 합판과 섬유판에 천연무늬단판을 접착한 목질마루판에 의해 시험을 실시하였다. 그 결과는 화학양론적으로 멜라민-요소와 포름알데히드간의 비율이 적정한 조건에서 반응이 충분히 일어난 경우에 상태접착력, 준내수접착력, 포름알데히드 방출량 등이 가장 양호하게 나타났다. 복합마루판의 평면인장강도는 각 몰비에서 14 kgf/cm2를 상회하였으며, 포름알데히드 방출량은 1.0몰비에서 9.53 mg/L로 가장 낮게 나타났다. 합판마루판의 평면인장 접착력 시험에서는 1.4몰비에서 14.02 kgf/cm2로 가장 높은 값을 보였다. 합판마루판의 포름알데히드 방출량 조사에서도 1.0목비에서 0.26 mg/L로 가장 낮게 나타났다.